1985
DOI: 10.5962/bhl.title.132962
|View full text |Cite
|
Sign up to set email alerts
|

Genetic methods for the control of Lepidopteran species : status and potential

Abstract: Lepidopteran species are widely recognized as the most important pests of many major crops, forests, and stored products. Three genetic control methods that have been developed and field tested against Lepidopteran pests are the sterile insect technique, inherited sterility, and backcross sterility. This report presents the principles, advantages, and disadvantages of each of these methods and the potential of using the methods against Lepidopteran pests .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 35 publications
1
73
1
Order By: Relevance
“…Smith)] were irradiated with sub-sterilizing doses of radiation (LaChance 1985, Arthur et al 1990, Arthur et al 1991. The overall low survivorship in the field trial indicates that large numbers of eggs would need to be used to have sufficient numbers oflarvae to serve as hosts for C. plutellae.…”
Section: Discussionmentioning
confidence: 99%
“…Smith)] were irradiated with sub-sterilizing doses of radiation (LaChance 1985, Arthur et al 1990, Arthur et al 1991. The overall low survivorship in the field trial indicates that large numbers of eggs would need to be used to have sufficient numbers oflarvae to serve as hosts for C. plutellae.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, successful sterile males mating a wild female produce a large number of offspring biased towards males (depending on dose) and sterile at F 2 . It may be necessary to take crop damage from F 1 larvae into account (LaChance 1985), although during an eradication this should be of short duration. In addition, a synergistic benefit of the combination of two tactics has been demonstrated to occur, for example where sterile eggs oviposited by released sterile females have been shown to enhance the numerical response of egg parasitoids (Bloem et al 1998;Cossentine and Jensen 2000).…”
Section: Operational Strategiesmentioning
confidence: 99%
“…Previous investigations have showed that the SIT would be more effective if only males were released (LaChance 1979). Proverbs and Newton (1962) and Rananavare et al (1989) reported that the release of completely sterile Cydia pomonella L. (Lepidoptera: Tortricidae) and P. operculella males was more effective than the release of males together with the females.…”
Section: Introductionmentioning
confidence: 99%